Contribution to Electrical System Inertia of Dual Fuel two-stroke Engines in Isolated Grid: A Case Study - D’Agostino Fabio; Gabriele Bruno; Silvestro Federico; Trasverso Alberto; Sala Silvio (E3S Web of Conferences, 2023)
The paper analyzed the dynamic performance of dual two-stroke engines with respect to classical Diesel gensets and the contribution to increase the rotating inertia of an isolated electrical grid with significant penetration of Renewable Energy Sources (RESs). The role of genset capable to provide better inertia and primary frequency regulation is essential for the integration of renewable generation in order to provide frequency stability and better power quality.